Analisis Finansial Industri Rumah Kayu CV Rajawali Tunggal Perkasa di Desa Woloan 1 Utara Kecamatan Tomohon Barat. - M. Kisal M. Soemingkar; Eyverson Ruauw; Juliana R. Mandey; Leonardus R. Rengkung (COCOS, 2014)
AbstractThe objective of this research is to find out the feasibility of CV Rajawali Tunggal Perkasa wooden house business in North Woloan 1 village, West Tomohon sub District. The research was done for nine months, from February, 2014 to October, 2014. Source of data used were primary data and secondary data related to this research. Data was analyzed by using financial analysis methods, comprising of Net Present Value (NPV), Internal Rate of Return, Benefit-Cost Ratio (B/C Ratio), Payback Period (PBP), and Sensitivity Analysis.CV Rajawali Tunggal Perkasa wooden house business has an NPV of (Rp 17.908.125.332), B/C Ratio of 1,9 and a Payback Period of 0,283 years which mean that the company has redeemed its investment before the project ends. Results of the financial analysis showed that CV Rajawali Tunggal Perkasa wooden house business was feasible to develop and it’s business is sensitive to price of raw materials increase over 307,8812612145 percent and the selling price of wooden houses decrease by 62,43396290039 percent.Keywords : financial analysis, industry, wooden house